2001
DOI: 10.1042/bst029a083
|View full text |Cite
|
Sign up to set email alerts
|

Tyrphostins: inhibitors of membrane traffic pathways?

Abstract: Several intracellular membrane trafficking events are mediated by tyrosine-containing motifs within the cytosolic domains of integral membrane proteins. Many such motifs conform to the consensus YXX+(+ represents a bulky hydrophobic residue). This motif interacts with the medium chain (mu) subunits of adaptor complexes which link the cytosolic domain of the integral membrane protein to the clathrin coat involved in vesicle formation. The motif YXX+ is similar to motifs which are phosphorylated by tyrosine kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…TyrA23 can specifically prevent the interaction between cargo motifs destined for endocytosis and the m2 subunit of the clathrin binding AP-2 adaptor complex (Banbury et al, 2003). A recent report showed that TyrA23 efficiently inhibited interaction between the human transferrin receptor and a m-adaptin subunit and then blocked the internalization of the human transferrin receptor in Arabidopsis protoplasts (Ortiz-Zapater et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TyrA23 can specifically prevent the interaction between cargo motifs destined for endocytosis and the m2 subunit of the clathrin binding AP-2 adaptor complex (Banbury et al, 2003). A recent report showed that TyrA23 efficiently inhibited interaction between the human transferrin receptor and a m-adaptin subunit and then blocked the internalization of the human transferrin receptor in Arabidopsis protoplasts (Ortiz-Zapater et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…TyrA23 is thought to block specifically the interaction of endocytic cargo motifs with the clathrin medium chain. This interaction is crucial for establishing a link between the cytosolic domains of membrane proteins to the clathrin coat involved in vesicle formation (Banbury et al, 2003). Exposure of seedlings to TyrA23 led to an overall decrease in GFP-PIP2;1 diffusion coefficients, with Ĝ reduced to 1.59 3 10 23 mm 2 /s (SE 1.41 to 1.78 3 10 23 mm 2 /s) ( Figure 9A; see Supplemental Movie 6 online).…”
Section: Membrane Rafts and Clathrin Contribute To The Internalizatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations of the YXXF motif abolish the interaction with m (Ohno et al, 1995;Boll et al, 1996;Stephens et al, 1997) and alter the subcellular localization of the cargo proteins (Bos et al, 1993;Humphrey et al, 1993). The interaction of m with cargo proteins through the YXXF motif is disrupted by the structural Tyr analog Tyrphostin A23 (TyrA23), which is an efficient inhibitor of clathrin-mediated endocytosis (Banbury et al, 2003). Evidence for the importance of AP-2 during development is suggested by studies of mutants with disrupted subunit genes.…”
Section: Introductionmentioning
confidence: 99%
“…To examine whether the plasma membrane localization of AP2M-GFP is dependent on the interaction with cargo proteins, the root tip cells of the AP2M-GFP ap2m seedlings were incubated with the clathrinmediated endocytosis inhibitor TyrA23. Tyrphostin A51 (TyrA51), which has no effect on the interaction between AP-2 and cargo proteins (Banbury et al, 2003), was used as the negative control. TyrA23 significantly reduced the AP2M-GFP fluorescence at the plasma membrane in a time-dependent manner, although the fluorescence at the plasma membrane was not altered by TyrA51 even after the 2-h incubation ( Figure 1C).…”
Section: Arabidopsis Ap2m Localizes At the Plasma Membrane In A Tyra2mentioning
confidence: 99%